Urban logistics - "Browne, Michael (ed.); Behrends, Sonke (ed.);Woxenius, John " (Great Britain, 2019)
Approximately 80 per cent of European and American citizens live in an urban environment. Due to their large populations and extensive commercial establishments, urban areas require large quantities of goods and services for commercial and domestic use. This results in increasing levels of demand for freight transport services. Freight transport in towns and cities is a major contributor to environmental impacts, particularly to local air pollution and noise. Urban Logistics addresses public policy makers, freight transport companies and receivers of supplies, providing them with the information and guidance to affect change in the logistics of the city.
Keywords: Urban transportation-Planning